El Ocultamiento de Información en Declaraciones Juramentadas y su repercusión legal en el Ámbito Penal - Ronnie Marcelo, Montero Sánchez (2021)
ABSTRACT: This research work is structured in three chapters. The first chapter refers to the study of the sworn statements themselves, their definition, types, characteristics and elements, as well as the identification of the competent authorities to these statements can be made, and the circumstances and elements that must be met in order to make a sworn statement before the General State Comptroller and Notary Publics. In the second chapter, the analysis of the concealment of information in sworn statements was carried out, reviewing definitions of both "concealment" and "falsehood", in order to later detect the differences between both conducts, reaching the conclusion that falsehood is the mother behavior and that concealment is derived from it. The third chapter is the most extensive and contains a study of the criminal consequences of concealing or falsifying information in sworn statements, for which it was necessary to review the scope of the criminally relevant conduct, as well as the authorship and participation of the active subject, to conclude with an analysis of the typicality, unlawfulness, and exhaustiveness that may exist if the conduct of concealing information falls within the criminal definition of perjury, with the aim of finding a possible criminal liability for those who conceal information in sworn statements.